2016
DOI: 10.5114/kitp.2016.62607
|View full text |Cite
|
Sign up to set email alerts
|

Application of the CardioCel bovine pericardial patch – a preliminary report

Abstract: IntroductionAnimal pericardial patches are widely used in adult and pediatric cardiac surgery. A search is ongoing for a new material with optimal surgical properties that will reduce intraoperative bleeding and the occurrence of restenosis, calcification, and pseudoaneurysms in long-term observation. One product of interest is the CardioCel bovine pericardial patch.AimEvaluation of the short-term results of CardioCel bovine pericardial patch implantation during pediatric cardiac surgery.Material and methodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The ADAPT tissue-engineered bovine pericardium bio-scaffold (CardioCel) is distinct from comparable patches by the removal of calcium-binding phospholipids and antigens during manufacture, both of which are known to promote the calcification observed with other patches [ 13 , 16 ]. Recent data from the extension study of the Phase II trial of CardioCel in CHD repair reported no calcification or repeat surgery across 14 patients followed-up for between five and eight years [unpublished data, [ 17 ]].…”
Section: Introductionmentioning
confidence: 99%
“…The ADAPT tissue-engineered bovine pericardium bio-scaffold (CardioCel) is distinct from comparable patches by the removal of calcium-binding phospholipids and antigens during manufacture, both of which are known to promote the calcification observed with other patches [ 13 , 16 ]. Recent data from the extension study of the Phase II trial of CardioCel in CHD repair reported no calcification or repeat surgery across 14 patients followed-up for between five and eight years [unpublished data, [ 17 ]].…”
Section: Introductionmentioning
confidence: 99%
“…Stenosis at the anastomotic site was observed in 2 patients soon after surgery, however, at a follow-up of a median of 58 (range 14-219) days, no patient demonstrated failure of repair or required reintervention. 14…”
Section: Resultsmentioning
confidence: 99%
“…These complications were often related to high pressure conditions, which could be indicative of the low performance due to insufficient mechanical properties of the source of tissue, as observed in vitro 205 . Therefore, crosslinked materials with enhanced mechanical properties, like bovine pericardium, that include processing steps preventing crosslinker‐related complications (eg calcification 211 ) have been developed, which have shown positive short‐term results in paediatric cardiovascular applications, 211‐213 but long‐term assessment is required.…”
Section: Xenografts In Clinical Indicationsmentioning
confidence: 99%